Dispute Mediator in the Digital Space: Can The “Dewan Media Sosial” (DMS) Fulfill Its Duties? - Panji Putra Ariyanto; Fatlurrahman (Abjad Journal of Humanities & Education, 2024)
The "Dewan Media Sosial" (DMS) is a groundbreaking initiative designed to mediate disputes in the digital realm, particularly on social media in Indonesia. This paper critically assesses the DMS's potential to effectively carry out its responsibilities. It examines the DMS's strengths, including its specialized focus on digital conflicts, accessibility, technological integration, and potential to gain public trust and credibility. However, it also identifies significant challenges, such as the need for a solid regulatory and legal framework, ensuring impartiality and fairness, scalability, and protecting privacy and security. The paper concludes that although the DMS shows promise as a transformative entity for digital dispute resolution, its success depends on addressing these key challenges. Recommendations include fostering stakeholder collaboration, continuous monitoring and adaptation, and enhancing public awareness and education. The analysis emphasizes that if these issues are effectively managed, the DMS has the potential to create a more harmonious and accountable online environment. Keywords : Dewan Media Sosial (DMS, Dispute mediation, Digital space, Regulatory framework, Public trust